Transformasi Pelayanan Kesehatan Primer melalui Metode Inovatif Irene's Donuts untuk Meningkatkan Kesadaran Ibu dalam Mengurangi Faktor Risiko Karies Anak di Kota Banda Aceh - Reca, Reca; Salfiyadi, Teuku; Nuraskin, Cut Aja; Rahayu, Eka Sri; Dzaki, Muhammad Haikal (PT. Riset Press International, 2024)
Irene’s Donuts is an interactive program designed in both computer and manual formats, aimed at providing understanding of the risk factors for dental caries in children from an early age. This program emphasizes the importance of early prevention through the active involvement of parents, particularly mothers. The community service initiative aims to transform primary healthcare services through the innovative method of Irene’s Donuts to raise awareness among mothers about reducing the risk factors for caries in children in Banda Aceh. This community service is conducted using a descriptive method, targeting children and their mothers as respondents. Data analysis employs univariate analysis. The interventions provided include problem-based counseling, measuring children’s caries risk scores, and demonstrating proper tooth brushing techniques. The results of the community service show a significant increase in knowledge, attitudes, and practices of mothers regarding the maintenance of their children’s dental and oral health after the intervention using the Irene’s Donuts method. Additionally, there was a decrease in the caries risk scores among children, indicating the effectiveness of this method in reducing risk factors for caries and improving overall dental and oral health in children.